Minat Beli Konsumen Pada Produk Rengginang Ikan Tenggiri Khas Probolinggo - Elmas, Muhammad Syarif Hidayatullah (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
This study attempts to know the quality of product and price to consumers purchasing interest, either in the simultaneous and partial .The sample used in this research 30 respondents. The method of analysis of the data using the validity and reliability test, the classical assumption, and with the help of the multiple linear regression spss 22.0 version for windows. The results of tests indicated that the product quality and price significant simultaneously with the level of significance of 0,000 < 0,05 consumers purchasing interest. While based on partial shows that the product quality and price significant of the significance of 0,000 < 0,05 and 0,005 < 0,05 to consumers purchasing interest.